Natural and synthetic poly(malic acid)-based derivates: a family of versatile biopolymers for the design of drug nanocarriers*. (August 2014) - Loyer, Pascal; Cammas-Marion, Sandrine
Abstract The field of specific drug delivery is an expanding research domain. Besides the use of liposomes formed from various lipids, natural and synthetic polymers have been developed to prepare more efficient drug delivery systems either under macromolecular prodrugs or under particulate nanovectors. To ameliorate the biocompatibility of such nanocarriers, degradable natural or synthetic polymers have attracted the interest of many researchers. In this context, poly(malic acid) (PMLA) extracted from microorganisms or synthesized from malic or aspartic acid was used to prepare water-soluble drug carriers or nanoparticles. Within this review, both the preparation and the applications of PMLA derivatives are described emphasizing the in vitro and in vivo assays. The results obtained by several groups highlight the interest of such polyesters in the field of drug delivery.